2005
DOI: 10.1084/jem.20050128
|View full text |Cite
|
Sign up to set email alerts
|

IL-18–induced CD83+CCR7+ NK helper cells

Abstract: In addition to their cytotoxic activities, natural killer (NK) cells can have immunoregulatory functions. We describe a distinct “helper” differentiation pathway of human CD56+CD3− NK cells into CD56+/CD83+/CCR7+/CD25+ cells that display high migratory responsiveness to lymph node (LN)–associated chemokines, high ability to produce interferon-γ upon exposure to dendritic cell (DC)- or T helper (Th) cell–related signals, and pronounced abilities to promote interleukin (IL)-12p70 production in DCs and the develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
262
1
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(284 citation statements)
references
References 58 publications
19
262
1
1
Order By: Relevance
“…Using blocking antibodies, we demonstrated that both DC-derived IL-12 and IL-18 are necessary for IFN-g secretion by a subpopulation of NK cells. Addition of rIL-12 to the supernatant of TNF-a/PGE2-matured DC did not result in NK-cell IFN-g production (data not shown), which indicates that both IL-12 and IL-18 are required to induce IFN-g secretion, supporting the two-signal requirement mechanism described by Mailliard et al [6]. Notably, the IFN-g-producing NK-cell population contained both NK cells with an intermediate and with a high expression of CD56, which is remarkable since the CD56 bright subpopulation has been described as the cytokine-producing population after NK-DC interaction [38].…”
supporting
confidence: 78%
See 2 more Smart Citations
“…Using blocking antibodies, we demonstrated that both DC-derived IL-12 and IL-18 are necessary for IFN-g secretion by a subpopulation of NK cells. Addition of rIL-12 to the supernatant of TNF-a/PGE2-matured DC did not result in NK-cell IFN-g production (data not shown), which indicates that both IL-12 and IL-18 are required to induce IFN-g secretion, supporting the two-signal requirement mechanism described by Mailliard et al [6]. Notably, the IFN-g-producing NK-cell population contained both NK cells with an intermediate and with a high expression of CD56, which is remarkable since the CD56 bright subpopulation has been described as the cytokine-producing population after NK-DC interaction [38].…”
supporting
confidence: 78%
“…Recent studies suggest that the interplay between NK cells and DC, the specialized antigenpresenting cell of the innate immune system [2], is critical in shaping the adaptive immune response [3]. This concept originates from several lines of evidence including: the discovery of NK cells colocalizing with DC in the T-cell areas of lymph nodes [4,5], the coupling of NK-cell recruitment to lymph nodes with the induction of more potent Th1 skewing [3], and the identification of NK-cell subpopulations with helper properties [6]. Although the exact mechanisms of NK-DC interaction remain to be elucidated, increasing evidence supports the importance of bidirectional NK-DC crosstalk [7,8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, we observed differential expression of ICAM-1 and LFA-1, which is consistent with the functional divergent activities of CD56 bright and CD56 dim subsets [7]. According to its cytotoxic effector function [41], CD56 dim from PB and PF expressed high LFA-1 levels, whereas NK-mediated helper functions may be related to the high ICAM-1 levels on CD56 bright [42]. Accordingly, IFN-g production was also ascribed to CD56 bright subset [10].…”
Section: Discussionsupporting
confidence: 82%
“…Mature NK cells cultured in the presence of cytokines express markers such as HLA-DR [8] and NKp44 [23] that were downregulated during progression of pre-NK cells to more mature developmental stages [19]. Furthermore, CD56 dim upregulate CD56 after activation by cytokines [24], downregulate CD16 after contact with target cells [25] and acquire receptors to home to lymph nodes after stimulation with IL-18 [26]. Hence, classifying activated NK cells by differentiation stage is cumbersome.…”
Section: Introductionmentioning
confidence: 99%